KONSEP PENDIDIKAN ‘HADAP-MASALAH’ PAULO FREIRE DAN RELEVANSINYA BAGI PENDIDIKAN DI INDONESIA (Telaah Filosofis-Kritis atas Relasi Guru dan Murid di Masa Pandemi Covid-19) - Romanus Piter; Magnus Mitan (Aggiornamento, 2020)
Focus of this paper is a problem in the learning process applied in Indonesia today, especially in teacher-student relations. The goal to be achieved is to find solutions in the form of philosophical-critical ideas that are appropriate in the learning process at school or campus, especially with the Work From Home (WFH) system, in order to improve the quality of education in Indonesia. The methodology used is an analysis of the problems in the education system in Indonesia today using the concept of "problem-posing" education according to Paulo Freire. The findings in this paper are that the education system applied in Indonesia currently still uses the old or conservative method, namely teacher-centered and teachers have not maximally utilized existing digital technology. These findings indicate that the education system applied in Indonesia must be replaced with a new system that is student-centered. The solution offered is a learning process that emphasizes dialogue between teachers and students and takes advantage of today's sophisticated digital technology, especially during the WFH era. That way the quality of education in Indonesia is reflected in the mastery of science and technology.